Perancangan UI/UX Aplikasi Antrian Bengkel Jaya Toga Menggunakan Design Thinking - Arya Darma Saputra; Erika Putri Say; Jennifer .; Ahmad Farisi (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
In the digital era, User Interface (UI) and User Experience (UX) design play a crucial role in the development of both web and mobile applications. The advancement of digital technology also drives the need for efficient, easy-to-use, and user-centered service systems. Bengkel Jaya Toga still relies on pen and paper to manage customer vehicle queues, which potentially leads to issues such as disorganized queuing and the loss of daily reports. This research aims to design the UI/UX for the Bengkel Jaya Toga queuing and booking application by implementing the Design Thinking method. This method involves five steps: empathize, define, ideate, prototype, and testing, which are key to understanding user needs. Data collection was conducted through observation, interviews, and literature studies. The result of this research is a UI/UX design that includes service booking features, service queue management, service reports, and real-time service status information. Testing of the design indicates that the application design can improve service efficiency, ease of use, and user experience. Thus, the application of the Design Thinking method has proven effective in producing a UI/UX design that meets user needs and supports the improvement of service quality at Bengkel Jaya Toga.